Evaluasi Penggunaan Antibiotik Profilaksis pada Pasien Bedah Orthopedi Kategori Highly Recommended di IBS RSUP Prof.Dr.R.D. Kandou Manado - Tjitrosantoso, Heedy; Tampa, Randy; Sumual, Amelia J (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2024)
Surgical Wound Infection is an infection that occurs in the incision site or area due to an operation or surgery obtained after surgery. The risk of this infection can be reduced by administering prophylactic antibiotics. The administration of prophylactic antibiotics is aimed at reducing and preventing surgical wound infections, inhibiting the emergence of resistance, reducing patient morbidity and mortality, and minimizing health care costs. Prophylactic administration of antibiotics in the Highly Recommended category of surgical procedures has been shown to be effective. This study aims to evaluate the use of prophylactic antibiotics in orthopedic surgery patients in the Highly Recommended category at the Central Surgery Installation (IBS) Prof. Dr. R. D. Kandou Manado Hospital. This research is an observational study. Data were obtained retrospectively by tracing the medical records of orthopedic surgery patients in the Highly Recommended category for the period March – July 2023 using a purposive sampling method which was then analyzed descriptively using the General Guidelines for the Use of Antibiotics 2011 from the Ministry of Health and the Clinical Practice Guidelines for Antimicrobial Prophylaxis in Surgery 2013. From the results of the research conducted, data were obtained from 71 patients who used prophylactic antibiotics in 6 surgical procedures orthopedic category Highly Recommended. The most commonly performed surgical procedure was open reduction internal fixation (69.01%). From the results of the evaluation of the use of prophylactic antibiotics, 54 (76.06%) types of antibiotics were obtained, 54 (76.06%) doses of antibiotics, 71 (100%) routes of administration, 71 (100%) time of administration and duration giving 71 (100%). Overall, the use of prophylactic antibiotics is not fully in accordance with applicable guidelines, especially in the selection of types and doses of prophylactic antibiotics.